Sensing of Ce(iii) using di-naphthoylated oxacalix[4]arene via realistic simulations and experimental studies. (30th November 2017) - Panchal, Manthan; Kongor, Anita; Athar, Mohd; Mehta, Viren; Jha, P. C.; Jain, V. K.
Abstract : Here, we report a fluorescent sensor for the detection of Ce(iii ) using di-naphthoylated oxacalix[4]arene (DNOC). Abstract : Here, we report a fluorescent sensor for the detection of Ce(iii ) using di-naphthoylated oxacalix[4]arene (DNOC). Formation of the DNOC-Ce(iii ) complex has been confirmed by 1 H NMR and mass spectroscopic observations. A dramatic decrease in the emission intensity of DNOC is observed for Ce(iii ) with no competitive interference due to other divalent and trivalent ions. The linear range of detection was obtained over a concentration range between 18 nM and 2 μM. Furthermore, density functional theory (DFT)-based quantum mechanical calculations were executed to predict the most probable structure of the host–guest system. As the molecular geometry suggests, the nitro groups of DNOC bent and the naphthoyl groups (oxygen centres of alternate calixarene rings) stabilize the cerium inclusion complex in the 1, 3-alternate conformation. Thus, a novel analytical approach has been developed for Ce(iii ) detection using the oxacalixarene framework in solution. Moreover, the selective behaviour of DNOC also facilitates new opportunities for determining Ce(iii ) in a wide range of real samples.